Bacteria are important dimethylsulfoniopropionate producers in marine aphotic and high-pressure environments - Yanfen Zheng (Nature Portfolio, 2020)
Dimethylsulfoniopropionate (DMSP) is an osmolyte produced by marine microbes that plays an important role in nutrient cycling and atmospheric chemistry. Here the authors go to the Mariana Trench—the deepest point in the ocean—and find bacteria are key DMSP producers, and that DMSP has a role in protection against high pressure.